Access to Health Care for Migrants Along the Mexico-United States Border: Applying a Framework to Assess Barriers to Care in Mexico - Infante, César; Vieitez-Martinez, Isabel; Rodríguez-Chávez, César; Nápoles, Gustavo; Larrea-Schiavon, Silvana; Bojorquez, Ietza (Frontiers in Public Health, 2022)
Background Migrants in Mexico are entitled to care at all levels, independently of their migration status. However, previous studies show that access to care is difficult for this population. As the movement of in-transit migrants and asylum seekers has been interrupted at the Mexico-United States border by migration policies such as the “Remain in Mexico” program, and by border closures due to the COVID-19 pandemic, the Mexican health system has the challenge of providing them with health care. Levesque et al.'s framework, according to which access occurs at the interface of health system characteristics and potential users' abilities to interact with it, is a useful theoretical tool to analyze the barriers faced by migrants. Objective The objective of this article is to analyze the barriers to access the public Mexican health system, encountered by migrants in cities in Mexican states at the Mexico-United States border during the COVID-19 pandemic. Methods Data came from a multiple case study of the response of migrant shelters to health care needs during the COVID-19 pandemic. The study consisted of a non-probability survey of migrants with a recent health need, and interviews with persons working in civil society organizations providing services to migrants, governmental actors involved in the response to migration, and academics with expertise in the subject. We analyzed the quantitative and qualitative results according to Levesque et al.'s framework. Results 36/189 migrants surveyed had sought health care in a public service. The main limitations to access were in the availability and accommodation dimension (administrative barriers decreasing migrants' ability to reach the system), and the affordability dimension (out-of-pocket costs limiting migrants' ability to pay). Civil society organizations were a major source of social support, helping migrants overcome some of the barriers identified. Conclusions While Mexico's health regulations are inclusive of migrants, in practice there are major barriers to access public health services, which might inhibit migrants from seeking those services. In order to comply with its commitment to guarantee the right to health of all persons, the Mexican health authorities should address the implementation gap between an inclusive policy, and the barriers to access that still remain.